Mount Kelud in Dark Tourism Ethical Perspective - Mokodongan, Trisagia; Masjhoer, Jussac Maulana (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Dark tourism is a type of tourism that involves traveling to sites where death, suffering, tragedy, disaster, or violence occur. Indonesia can develop illicit tourism, one of which is Mount Kelud. Dark tourism has caused controversy in its development, especially regarding the ethical dimension. The study aims to identify the ethics of exploiting the suffering of victims and the motivation of tourists in Mount Kelud. It uses the systematic literature review method from articles, proceedings, and other scientific works sourced from scientific publications. Based on the analysis results, there was no exploitation element from the Mount Kelud eruption victims. The economic benefits of tourism directly help people recover from trauma. In addition, the community has instilled the value of harmonization to coexist with the volcano. Most tourists’ motivation is to satisfy their curiosity about the eruption of Mount Kelud, and there is no deviant motivation